‏Association between body mass index and cardiovascular risk factors in patients with type 2 diabetes mellitus (Latakia University Journal -Medical Sciences Series, 2021)
Background: Obesity is the major potentially modifiable risk factor for type 2 diabetes mellitus.Aim: The aim of this study was to assess the impact of overweight and obesity on glycaemic control and cardiovascular risk factors.Results: Of patients with type 2 diabetes, 21% were normal weight, 43% overweight (BMI 25-29.9 kg/m2), and 36% were obese (BMI ≥30 kg/m2)Overweight and obese patients with type 2 diabetes were younger, had poorer glycaemic control, higher blood pressures, and worse lipid profiles compared to patients with BMI